Pengelolaan Sampah Plastik Rumah Tangga dalam Rangka Pencegahan Pencemaran Lingkungan (Study di Lingkungan Kelurahan Pedungan Kecamatan Denpasar Selatan Kota Denpasar) - I Made Ode Dwiyana Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Plastic waste is waste that cannot be decomposed and is very dangerous to environmental health conditions because it is a non-organic waste. Prevention of environmental pollution occurs due to littering. Especially problems in the management of waste generated by households. This study aims to analyze the policy of managing household plastic waste as an effort to prevent environmental pollution in the Pedungan Village area of ​​Denpasar City and to explain the factors that influence the management of household plastic waste in Pedungan Village. This study uses empirical legal research. The approach to the problem used is a fact approach, a case approach and a sociological approach. The data used are primary and secondary data. Data were analyzed and arranged systematically using qualitative analysis, namely by analyzing data obtained from primary and secondary data sources. The results showed that the Pedungan Urban Village area has issued a policy regarding the Decree of the Head of the Pedungan Village Number: 660/04 / I / 2019 concerning the Management Structure of the Pedungan Asri Waste Bank in Pedungan Village. This waste bank is responsible for managing plastic waste in the Pedungan village. The waste bank accepts plastic waste to be recycled back into goods that have more useful and economic value. The two factors that affect the management of plastic waste in the Pedungan Village area include local residents and immigrants.